2021
DOI: 10.1002/ped4.12294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and effectiveness of antiviral agents in hospitalized children with infectious mononucleosis in China: A multicenter retrospective study

Abstract: Importance The clinical characteristics of infectious mononucleosis (IM) in Chinese children have not been evaluated in multicenter studies, and the effectiveness of antiviral treatment are controversial. Objective To investigate the clinical characteristics of Chinese children with IM and current status of antiviral therapy for affected patients. Methods Hospitalized patients with IM were enrolled between 2018 and 2020 in five children’s hospitals in China. The clinical characteristics were compared among fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…In terms of the at-risk age of onset, our results showed that children hospitalized for IM were mainly 4–6 years old in China, which was similar to the data analyzed by the single-center study of hospitalized IM children ( Gao et al., 2011 ; Hu et al., 2021 ). In China and other developing countries of Asia and Africa, most primary EBV infections occur in children, especially preschoolers, who make up a large portion of IM patients ( Dunmire et al., 2015 ; Shi et al., 2022 ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In terms of the at-risk age of onset, our results showed that children hospitalized for IM were mainly 4–6 years old in China, which was similar to the data analyzed by the single-center study of hospitalized IM children ( Gao et al., 2011 ; Hu et al., 2021 ). In China and other developing countries of Asia and Africa, most primary EBV infections occur in children, especially preschoolers, who make up a large portion of IM patients ( Dunmire et al., 2015 ; Shi et al., 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…Hu et al. analyzed the epidemiological characteristics of children hospitalized for IM in Beijing, China, and indicated that the male to female ratio was 1.6:1 ( Hu et al., 2021 ). Keun Hyung Son et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations